A Model for the Application of Interactive Digital Television to Communities of Practice - Braga, Marcus de Melo; Santos, Paloma Maria; Ferreira, Marcus Vinicius Anatócles da Silva; Dantas, Mario Antonio Ribeiro (International Journal of Advanced Corporate Learning (iJAC), 2010)
Communities of Practice make intensive use of information and communication technologies (ICT) to meet their needs of interaction among their members. At present, the main supporting tool for these communities is the Internet and the software tools available for their users. With the advent of digital TV, however, new resources have become available to these interactive communities. This study aims at analyzing the basic needs of technology support for virtual communities, identifying the essential software services that can meet these needs and propose an application model for interactive digital television that can meet the main needs of a Community of Practice. To achieve that, the essential services for a Community of Practice were identified by means of a field research applied to a knowledge management Community of Practice in order to propose an application model for Interactive Digital TV to Communities of Practice. The results discussed here may be used to develop applications for Interactive Digital TV and Communities of Practice, exploring the interactive resources of this new platform.